Quantum Ericson Engine with Multiple States in One Dimensional Potential Well - Nailul Hasan (Al-Fiziya: Journal of Materials Science, Geophysics, Instrumentation and Theoretical Physics, 2021)
A quantum ericson-engine that consists of a single particle with multiple states, has been explored. It is a quantum analogy to the classical ericson-engine consisting of a combination of two isothermal processes and two isobaric processes. By analogizing a particle in a one-dimensional infinite potential well as a gas in a piston-cylinder, quantum thermodynamic processes in a quantum ericson-engine can be explained from the analogies of classical processes such as isothermal, and isobaric.  The results of the research show that the thermal efficiency of the quantum ericson-engine has similarities with the classical ericson-engine.